A hospital staff scheduling problem under stochastic operation times. (2016) - Sarin, Subhash C.; Sherali, Hanif D.; Kim, Seon Ki
This paper is concerned with a hospital staff scheduling problem wherein surgical operation times are stochastic. We formulate a complete recourse, scenario-based model for this problem, and develop a branch-and-cut (B&C) algorithm that is further hybridised with the Monte Carlo method (MCM). The proposed hybrid MCM-based approach is demonstrated to substantially reduce the required computational effort over a purely branch-and-cut methodology while producing near-optimal solutions having relatively small optimality gaps.